Method for testing thermophysical properties of supercooled unstable hydrated salt system phase change material

By testing the phase change material of supercooled unstable hydrated salt system, pretreatment of heating and cooling is carried out below the material melting temperature range, the exothermic peak and endothermic peak in the DSC curve are separated, solving the data analysis deviation problem caused by the mixing of exothermic peaks and endothermic peaks in the prior art, and achieving more accurate thermal physical performance testing.

CN119901784AActive Publication Date: 2025-04-29QINGHAI INST OF SALT LAKES OF CHINESE ACAD OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510088103.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-29
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

When testing the thermal physical properties of phase change materials of supercooled unstable hydrated salt system, the exothermic peak of the DSC curve is mixed with the endothermic peak, resulting in the data analysis results being prone to deviations.

Method used

After the initial cooling of the material is completed, the pretreatment is carried out to raise the heat and cool down one or several times within the range below the melting temperature of the material to separate the exothermic peak from the endothermic peak to avoid interference from the exothermic peak on the endothermic peak.

Benefits of technology

The precise analysis of melt characteristic peaks by DSC is achieved, avoiding interference from exothermic peaks on endothermic peaks, and improving the accuracy of thermal physical performance testing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119901784A_ABST
    Figure CN119901784A_ABST
Patent Text Reader

Abstract

The invention discloses a method for testing thermophysical properties of a supercooled unstable hydrated salt system phase change material. The test method comprises the following steps: performing a first DSC cycle test on the supercooled unstable hydrated salt system phase change material: raising the temperature from an initial temperature to a first temperature, and then reducing the temperature to a second temperature; carrying out at least one pretreatment on the material obtained by the first DSC cycle test: raising the temperature from the second temperature to a third temperature, and then reducing the temperature to the second temperature; and performing DSC cycle test on the pretreated material. According to the method, at least one pretreatment of heating and then cooling is carried out in the range lower than the melting temperature of the material after initial cooling, so that separation of an exothermic peak and an endothermic peak is realized, and interference of the exothermic peak on the endothermic peak is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of performance testing of hydrated salt system phase change materials, and in particular relates to a method for testing the thermophysical properties of a supercooled unstable hydrated salt system phase change material. Background Art

[0002] At present, the thermophysical properties test of hydrated salt system phase change energy storage materials is usually achieved through differential scanning calorimetry (DSC). For supercooled and unstable hydrated salt systems, due to the influence of the material's supercooling, the material does not have time to undergo a crystallization phase change during the cooling process, which is reflected in the DSC curve as the absence of an exothermic peak. During the heating process, the material begins to undergo a crystallization phase change, resulting in the simultaneous appearance of an exothermic peak (crystallization process) and an endothermic peak (melting process) in the heating stage. In some cases, the exothermic peak and the endothermic peak are closely connected (partially overlapped), which interferes with the subsequent thermophysical properties analysis.

[0003] The thermophysical properties of hydrated salt system phase change energy storage materials (e.g., melting phase change enthalpy, melting temperature, crystallization phase change enthalpy, crystallization temperature) are mainly tested by DSC and T-History methods. The main difference between the two methods is the size of the research object. The sample amount required by T-History method (greater than tens or hundreds of grams) is about 10,000 times larger than that of DSC sample (DSC requires 1-20 mg of sample), but DSC method has faster measurement time and more accurate results. The vertical axis of the DSC curve represents the rate of heat absorption or heat release of the sample, and the horizontal axis represents temperature or time. Generally, a complete melting-solidification process (heating until the material is completely melted and then cooling until the material is completely crystallized) is a cycle. However, when the supercooling behavior of the material is unstable, there will be no exothermic peak in the cooling process, and a delayed exothermic peak in the heating process. Sometimes the material begins to melt again before it is completely crystallized, which will lead to coupling of exothermic peak and endothermic peak, which is easy to lead to deviation of analysis conclusions in actual data analysis.

[0004] To address this problem, existing technologies mainly involve crystallizing samples during sample preparation and performing only one DSC test. This method may result in inaccurate test results for samples that require DSC cycling. Alternatively, for samples that require cycling, the T-History method is used for macroscopic cycling, followed by a single DSC test. However, this method is not only time-consuming, but also requires a large amount of sample testing, which affects the uniformity of heating, and the interfacial water exchange caused by the sealing of the equipment affects the material's cycling performance, which has a certain impact on the test results. Summary of the invention

[0005] The main purpose of the present invention is to provide a method for testing the thermophysical properties of a supercooled unstable hydrated salt system phase change material to overcome the shortcomings of the prior art. The thermophysical properties of the existing supercooled unstable hydrated salt system phase change energy storage material are mainly tested by the DSC method. The main disadvantage of this method is that the exothermic peak and the endothermic peak in the DSC heating stage are mixed, which leads to deviations in the results during data analysis.

[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0007] The embodiment of the present invention provides a method for testing the thermophysical properties of a supercooled unstable hydrated salt system phase change material, which comprises:

[0008] Provide supercooled unstable hydrated salt system phase change materials;

[0009] The supercooled unstable hydrated salt system phase change material is subjected to a first DSC cycle test: the temperature is raised from a starting temperature to a first temperature, and then the temperature is lowered to a second temperature; wherein the starting temperature is lower than the phase change temperature of the supercooled unstable hydrated salt system phase change material, the first temperature is higher than the melting temperature of the supercooled unstable hydrated salt system phase change material, and the second temperature is lower than the melting temperature of the supercooled unstable hydrated salt system phase change material;

[0010] The material obtained from the first DSC cycle test is pretreated at least once: the temperature is raised from the second temperature to a third temperature, and then the temperature is lowered to the second temperature; wherein the third temperature is lower than the melting temperature of the supercooled unstable hydrated salt system phase change material;

[0011] And, the DSC cycle test was carried out on the pretreated materials.

[0012] The embodiment of the present invention also provides the application of the aforementioned method for testing the thermophysical properties of supercooled unstable hydrated salt system phase change materials in testing the cyclic performance of materials with supercooled instability.

[0013] Compared with the prior art, the beneficial effect of the present invention lies in that: the present invention provides a method for pre-treating the material by heating and then cooling it once or several times within a range below the melting temperature of the material after the material completes the initial cooling, thereby separating the exothermic peak and the endothermic peak, avoiding the interference of the exothermic peak on the endothermic peak, and realizing the accurate analysis of the melting characteristic peak by DSC. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0015] Figure 1 is a DSC curve diagram of the first cycle of the sodium acetate trihydrate system phase change energy storage material in Example 1 of the present invention;

[0016] Figure 2 is a DSC curve diagram of the second cycle of the sodium acetate trihydrate system phase change energy storage material in Example 1 of the present invention;

[0017] Figure 3 It is a DSC curve diagram of the sodium acetate trihydrate system after adding the temperature rise and fall program section (-50°C → 30°C → -50°C) in Example 1 of the present invention;

[0018] Figure 4 is a DSC curve diagram of the first cycle of the PCG-10% phase change system in Example 2 of the present invention;

[0019] Figure 5 is the DSC curve diagram of the 2nd, 50th and 100th cycles of the PCG-10% phase change system in Example 2 of the present invention;

[0020] Figure 6 It is a DSC curve diagram of the PCG-10% system after adding a temperature rise and fall program section (-50°C → 50°C → -50°C) in Example 2 of the present invention;

[0021] Figure 7 is a DSC curve diagram of the first cycle of the PCG-8% phase change system in Example 3 of the present invention;

[0022] Figure 8 is the DSC curve diagram of the 2nd, 50th and 100th cycles of the PCG-8% phase change system in Example 3 of the present invention;

[0023] Fig. 9 It is the DSC curve of the PCG-8% system after adding the temperature rise and fall program segment (-50°C→50°C→-50°C) in Example 3 of the present invention. DETAILED DESCRIPTION

[0024] In view of the defects of the prior art, the inventors of this case have proposed the technical solution of the present invention after long-term research and extensive practice. The main purpose of the present invention is to test the thermal physical properties of the existing supercooled unstable hydrated salt system phase change energy storage materials mainly through the DSC method. The main disadvantage of this method is that the exothermic peak and the endothermic peak in the DSC heating section are mixed, which leads to the problem of deviation in the results during data analysis. A pretreatment is designed to heat up and then cool down once or several times within a temperature range below the melting point of the material after the cooling section is completed, thereby achieving the separation of the exothermic peak and the endothermic peak and avoiding the interference of the exothermic peak on the endothermic peak.

[0025] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] One aspect of an embodiment of the present invention provides a method for testing the thermophysical properties of a supercooled unstable hydrated salt system phase change material, comprising:

[0027] Provide supercooled unstable hydrated salt system phase change materials;

[0028] The supercooled unstable hydrated salt system phase change material is subjected to a first DSC cycle test: the temperature is raised from a starting temperature to a first temperature, and then the temperature is lowered to a second temperature; wherein the starting temperature is lower than the phase change temperature of the supercooled unstable hydrated salt system phase change material, the first temperature is higher than the melting temperature of the supercooled unstable hydrated salt system phase change material, and the second temperature is lower than the melting temperature of the supercooled unstable hydrated salt system phase change material;

[0029] The material obtained from the first DSC cycle test is pretreated at least once: the temperature is raised from the second temperature to a third temperature, and then the temperature is lowered to the second temperature; wherein the third temperature is lower than the melting temperature of the supercooled unstable hydrated salt system phase change material;

[0030] And, the DSC cycle test was carried out on the pretreated materials.

[0031] In some more specific embodiments, the supercooled unstable hydrated salt system phase change material includes sodium acetate trihydrate hydrated salt system phase change energy storage material and / or hydrated salt system phase change gel composite material.

[0032] Furthermore, the hydrated salt system phase change gel composite material is prepared from a hydrated salt phase change energy storage material and an organic polymer.

[0033] Furthermore, the hydrated salt system phase change energy storage material includes sodium acetate trihydrate hydrated salt system phase change energy storage material and / or Mg(NO3)2·6H2O-MgCl2·6H2O magnesium-based eutectic salt phase change energy storage material, but is not limited thereto.

[0034] Furthermore, the hydrated salt system phase change gel composite material includes a magnesium-based eutectic salt phase change gel composite material and / or a sodium acetate trihydrate phase change gel composite material, but is not limited thereto.

[0035] In some more specific embodiments, the supercooled unstable hydrated salt system phase change material has supercooling instability.

[0036] In some more specific embodiments, when the supercooled unstable hydrated salt system phase change material is subjected to a DSC cycle test, no exothermic peak appears on the cooling section of its DSC curve, or the exothermic peak on the cooling section of its DSC curve is too small or incomplete and an exothermic peak appears in the heating section.

[0037] In some more specific embodiments, the testing method specifically includes:

[0038] The supercooled unstable hydrated salt system phase change material is subjected to a first DSC cycle test: the temperature is increased from the starting temperature to the first temperature at a heating rate of 5 to 15°C / min, and then the temperature is decreased to the second temperature at a cooling rate of 5 to 15°C / min.

[0039] Furthermore, the starting temperature is at least 20° C. lower than the phase change temperature of the supercooled unstable hydrated salt system phase change material.

[0040] Furthermore, the first temperature is higher than the melting temperature of the supercooled unstable hydrated salt system phase change material by more than 20°C.

[0041] Furthermore, the second temperature is at least 20° C. lower than the melting temperature of the supercooled unstable hydrated salt system phase change material.

[0042] In some more specific embodiments, the testing method specifically includes:

[0043] The material obtained from the first DSC cycle test is pretreated at least once: the temperature is increased from the second temperature to the third temperature at a heating rate of 5 to 15°C / min, and then the temperature is decreased to the second temperature at a cooling rate of 5 to 15°C / min.

[0044] Furthermore, the third temperature is 5-30° C. lower than the melting temperature of the supercooled unstable hydrated salt system phase change material.

[0045] In some more specific embodiments, the test method for the thermophysical properties of the supercooled unstable hydrated salt system phase change material includes:

[0046] (1) The newly prepared hydrated salt system phase change energy storage material is sampled for DSC cycle testing, and the program is set to "reach a certain temperature below the phase change temperature (starting temperature point) → heating to the highest temperature (first temperature) → cooling to the lowest temperature (second temperature)" as a complete cycle and multiple cycle tests are performed (greater than or equal to 2 times), where the "lowest temperature" is several tens of degrees lower than the melting temperature to ensure that the sample can achieve a crystallization phase transition, and the "highest temperature" is higher than the melting temperature to ensure that the sample can achieve a sufficient melting phase transition;

[0047] (2) obtaining a cyclic DSC curve of the thermophysical properties (melting enthalpy, melting temperature and solidification enthalpy, solidification temperature) of the sample through step (1);

[0048] (3) If, during multiple cycles, the exothermic peak of the sample appears in the cooling section, and only the endothermic peak appears in the heating section, the hydrated salt system is judged to have stable supercooling behavior; if the sample does not have an exothermic peak in the cooling section of the DSC curve, or the exothermic peak is obviously too small or incomplete, and an exothermic peak appears in the heating section, the hydrated salt system can be judged to have supercooling instability;

[0049] (4) For hydrated salt systems with supercooling instability, it is necessary to embed an additional program segment in the original program: "lowest temperature → heating to a temperature lower than the melting temperature (third temperature) → cooling to the lowest temperature" → heating to the highest temperature → cooling to the lowest temperature (the temperature in quotation marks is the embedded pretreatment heating and cooling cycle, and the pretreatment can also be repeated multiple times to ensure that the sample is fully crystallized). Performing multiple cycle tests for a complete cycle can ensure that in the measured DSC cycle curve, the exothermic peak appears in the cooling section and the endothermic peak appears in the heating section, without mutual interference.

[0050] The present invention aims at the problem that, during the cyclic performance test of the existing supercooled unstable hydrated salt system phase change energy storage material, due to the supercooling instability of the material, the cooling section of the DSC curve does not show an exothermic peak even if the temperature drops to far below the phase change temperature, and the material starts to delay the phase change during the heating process, resulting in the simultaneous appearance of an exothermic peak (solidification process) and an endothermic peak (melting process). In some cases, the exothermic peak and the endothermic peak are closely connected, which causes interference to the subsequent thermal physical performance analysis. The present invention provides a method for pre-treating the material by heating and then cooling once or several times within a temperature range below the melting point of the material after the initial cooling is completed, thereby separating the exothermic peak and the endothermic peak, thereby avoiding the interference of the exothermic peak on the endothermic peak.

[0051] For the hydrated salt system with supercooling instability, the present invention needs to embed an additional pretreatment program segment in the original program: "lowest temperature → heating to the highest temperature below the melting temperature → cooling to the lowest temperature". The pretreatment can also be repeated multiple times to ensure sufficient crystallization of the sample.

[0052] Another aspect of the embodiments of the present invention further provides the application of the aforementioned method for testing the thermophysical properties of supercooled unstable hydrated salt system phase change materials in testing the cyclic performance of materials with supercooled instability.

[0053] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.

[0054] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.

[0055] Example 1 Cyclic test of thermophysical properties of sodium acetate trihydrate (SAT) hydrated salt system phase change energy storage material

[0056] (1) Take a sample of the newly prepared sodium acetate trihydrate hydrate salt system phase change energy storage material and conduct DSC test ( Figure 1 ), the temperature range is 0℃→100℃→-50℃, and the thermophysical properties of the sample in the first cycle are obtained: melting enthalpy (287.5J / g), melting temperature (58.14℃, from Figure 1 It was found that the sample did not have an exothermic peak; the heating rate and cooling rate were both 10℃ / min;

[0057] (2) Continue to perform DSC test on the above samples ( Figure 2 ), the temperature range is -50℃→100℃→-50℃, and the DSC curve of the second cycle of the sample is obtained. At this time, the sample has two upward exothermic peaks during the heating process (-50℃→-20℃), and the exothermic peak is close to the endothermic peak at -18℃, indicating that the material system has supercooling instability;

[0058] (3) Cool the sample sodium acetate trihydrate from 100°C to -50°C ( Figure 3 The temperature is then raised to 30°C, which is 58°C below the melting temperature, and then lowered to -50°C ( Figure 3 Black dashed line), and finally heated to 100℃ ( Figure 3 Solid line), and the DSC curve of the sample is obtained. It can be found that there is only an endothermic peak in the heating process and it is no longer disturbed by the exothermic peak.

[0059] Example 2 Thermophysical properties test of hydrated salt system phase change gel composite material (PCG-10%)

[0060] (1) A phase change gel composite material (PCG-10%) was prepared from Mg(NO3)2·6H2O-MgCl2·6H2O magnesium-based eutectic salt phase change energy storage material and acrylamide (AAM), wherein the mass ratio of the magnesium-based eutectic salt phase change energy storage material to the sum of the monomer, the crosslinking agent, and the initiator was 100:10, the crosslinking agent was polyethylene glycol diacrylate (PEGDA), the initiator was 1-hydroxycyclohexyl phenyl ketone, and the composite ratio was m(monomer):m(crosslinking agent):m(initiator)=100:2:2; samples were taken for DSC test ( Figure 4 ), the temperature range is -30℃→90℃→-30℃, and the DSC curve of the first cycle of the sample is obtained. It is found from the figure that the sample does not have an exothermic peak; the heating rate and the cooling rate are both 10℃ / min;

[0061] (2) Continue to perform DSC cycle test on the above samples ( Figure 5 ), the temperature range is -50℃→90℃→-50℃, and the DSC curves of the 2nd, 50th, and 100th cycles of the sample are obtained. It can be clearly seen from the figure that the exothermic peak and the endothermic peak both appear in the heating stage of the DSC curve and are closely connected. The sample melts again as the temperature rises before it is completely crystallized, making it difficult to analyze the thermophysical properties of the sample at this time;

[0062] (3) In order to completely separate the exothermic peak and the absorption peak, the sample was first cooled from 90°C to -50°C ( Figure 6 The temperature is then raised to 50°C below the melting point, and then lowered to -50°C ( Figure 6 Black dashed line), and finally heated to 90℃ ( Figure 6 Solid line), and the DSC heating curve of the sample is obtained. It can be clearly seen from the figure that the separation of the exothermic peak and the endothermic peak in the heating stage is achieved, achieving the purpose of "only endothermic peak (melting phase change) in the heating stage", avoiding the interference of the exothermic peak on the endothermic peak.

[0063] Example 3 Thermal Physical Properties Test of Hydrated Salt System Phase Change Gel Material (Mg-PCG-8%)

[0064] (1) A phase change gel material (PCG-8%) was prepared from Mg(NO3)2·6H2O-MgCl2·6H2O magnesium-based eutectic salt phase change energy storage material and acrylamide (AAM) (mass ratio of 100:8), wherein the mass ratio of the magnesium-based eutectic salt phase change energy storage material to the sum of the monomer, the crosslinking agent, and the initiator was 100:8, the crosslinking agent was polyethylene glycol diacrylate (PEGDA), the initiator was 1-hydroxycyclohexyl phenyl ketone, and the composite ratio was m (monomer): m (crosslinking agent): m (initiator) = 100:2:2; samples were taken for DSC test ( Figure 7 ), the temperature range is -30℃→90℃→-50℃, and the DSC curve of the first cycle of the sample is obtained. It is found from the figure that the sample has only a weak exothermic peak, and it is impossible to judge whether the sample is completely crystallized; the heating rate and the cooling rate are both 10℃ / min;

[0065] (2) Continue to perform DSC test on the above samples ( Figure 8 ), the temperature range is -50℃→90℃→-30℃, and the DSC curves of the 2nd, 50th, and 100th cycles of the sample are obtained. It can be clearly seen from the figure that both the exothermic peak and the endothermic peak appear in the heating stage of the DSC curve, which interferes with the analysis of the endothermic and exothermic process of the sample;

[0066] (3) Cool the sample from 90℃ to -50℃ ( Fig. 9The temperature is then raised to 50°C below the melting point, and then lowered to -50°C ( Fig. 9 Black dashed line), and finally heated to 90℃ ( Fig. 9 Solid line), and the DSC heating curve of the sample is obtained. It can be clearly seen from the figure that the separation of the exothermic peak and the endothermic peak in the heating stage is achieved, achieving the purpose of "only endothermic peak (melting phase change) in the heating stage", avoiding the interference of the exothermic peak on the endothermic peak.

[0067] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0068] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.

Claims

1. A method for testing the thermophysical properties of a supercooled unstable hydrated salt system phase change material, characterized in that: include: Provide supercooled unstable hydrated salt system phase change materials; The supercooled unstable hydrated salt system phase change material is subjected to a first DSC cycle test: the temperature is raised from a starting temperature to a first temperature, and then the temperature is lowered to a second temperature; wherein the starting temperature is lower than the phase change temperature of the supercooled unstable hydrated salt system phase change material, the first temperature is higher than the melting temperature of the supercooled unstable hydrated salt system phase change material, and the second temperature is lower than the melting temperature of the supercooled unstable hydrated salt system phase change material; The material obtained from the first DSC cycle test is pretreated at least once: the temperature is raised from the second temperature to a third temperature, and then the temperature is lowered to the second temperature; wherein the third temperature is lower than the melting temperature of the supercooled unstable hydrated salt system phase change material; And, the DSC cycle test was carried out on the pretreated materials.

2. The testing method according to claim 1, characterized in that: The supercooled unstable hydrated salt system phase change material includes a hydrated salt system phase change energy storage material and / or a hydrated salt system phase change gel composite material.

3. The testing method according to claim 2, characterized in that: The hydrated salt system phase change gel composite material is made of hydrated salt phase change energy storage material and organic polymer; And / or, the hydrated salt system phase change energy storage material includes sodium acetate trihydrate hydrated salt system phase change energy storage material and / or Mg(NO3)2·6H2O-MgCl2·6H2O magnesium-based eutectic salt phase change energy storage material; And / or, the hydrated salt system phase change gel composite material includes a magnesium-based eutectic salt phase change gel composite material and / or a sodium acetate trihydrate phase change gel composite material.

4. The testing method according to claim 1, characterized in that: The supercooled unstable hydrated salt system phase change material has supercooled instability.

5. The testing method according to claim 1, characterized in that: When the supercooled unstable hydrated salt system phase change material is subjected to a DSC cycle test, no exothermic peak appears in the temperature-lowering section of the DSC curve, or the exothermic peak in the temperature-lowering section of the DSC curve is too small or incomplete and an exothermic peak appears in the temperature-raising section.

6. The testing method according to claim 1, characterized in that: Specifically include: The supercooled unstable hydrated salt system phase change material is subjected to a first DSC cycle test: the temperature is increased from the starting temperature to the first temperature at a heating rate of 5 to 15°C / min, and then the temperature is decreased to the second temperature at a cooling rate of 5 to 15°C / min.

7. The testing method according to claim 6, characterized in that: The starting temperature is lower than the phase change temperature of the supercooled unstable hydrated salt system phase change material by more than 20°C; And / or, the first temperature is higher than the melting temperature of the supercooled unstable hydrated salt system phase change material by more than 20°C; And / or, the second temperature is lower than the melting temperature of the supercooled unstable hydrated salt system phase change material by more than 20°C.

8. The testing method according to claim 1, characterized in that: Specifically include: The material obtained from the first DSC cycle test is pretreated at least once: the temperature is increased from the second temperature to the third temperature at a heating rate of 5 to 15°C / min, and then the temperature is decreased to the second temperature at a cooling rate of 5 to 15°C / min.

9. The testing method according to claim 8, characterized in that: The third temperature is 5 to 30° C. lower than the melting temperature of the supercooled unstable hydrated salt system phase change material.

10. Application of the method for testing the thermophysical properties of the supercooled unstable hydrated salt system phase change material according to claims 1 to 9 in testing the cyclic performance of materials with supercooled instability.

Citation Information

Patent Citations

  • Polylactic acid resin foam particle and polylactic acid resin foam particle molding

    CN103261299A

  • Differential scanning calorimetry DSC curve peak-splitting fitting method

    CN111781240A

  • Method for testing supercooling behavior stability of phase change energy storage material

    CN113390915A

  • Electrical conductivity fluorine polymer compsns.

    CN1397593A